Building Effective Employment Programs for Unemployed Youth in the Middle East and North Africa - Angel-Urdinola, Diego F.; Kuddo, Arvo; Semlali, Amina (Washington, DC: World Bank, 2013)
This study surveys active labor market programs (ALMPs) in selected countries of the Middle East and North Africa (MENA) region, identifies key challenges to their effective and efficient delivery, and proposes a policy framework for reforming public service provision. This study draws on data collected through surveys administered to public social, employment, and education agencies in selected MENA countries to identify key constraints and options for reforming publicly provided employment programs. Recent political transitions arising from the Arab Spring have contributed to the deterioration of labor market outcomes in the MENA region. In this context, ALMPs could become an important policy lever to address some of the challenges facing labor markets. These include: joblessness, skills mismatches, lack of labor market mobility, large and expanding informal sector, and lack of formal employment networks. The study also provides specific details on the beneficiaries, targeting, and expenditures of ALMPs during this same period.